2016
DOI: 10.1371/journal.pone.0162751
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Viruses in Mosquitoes from the Zambezi Valley of Mozambique

Abstract: Mosquitoes carry a wide variety of viruses that can cause vector-borne infectious diseases and affect both human and veterinary public health. Although Mozambique can be considered a hot spot for emerging infectious diseases due to factors such as a rich vector population and a close vector/human/wildlife interface, the viral flora in mosquitoes have not previously been investigated. In this study, viral metagenomics was employed to analyze the viral communities in Culex and Mansonia mosquitoes in the Zambezia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…The abundance and diversity of possible ISVs constituted a significant component of Culex mosquito viromes; for example, the virome of Culex spp. in Zambezi, Mozambique was dominated (88.5%) by them [48], whereas a study of the C. tritaeniorhynchus virome in Hubei, China also showed a conformable predominance (88%) of insect viruses [18]. In line with the reckonings, the result displayed a practically similar constitution, as much as 84%, 82%, and 100% of viruses were insect viruses, or had a high correlation with the mosquito virome previously identified, in C. tritaeniorhynchus, C. pseudovishnui, and C. inatomii, respectively (Supplementary Figure S4), implying a consistent virome composition in Culex mosquitoes, with slight variations possibly associated with the number of samples used.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance and diversity of possible ISVs constituted a significant component of Culex mosquito viromes; for example, the virome of Culex spp. in Zambezi, Mozambique was dominated (88.5%) by them [48], whereas a study of the C. tritaeniorhynchus virome in Hubei, China also showed a conformable predominance (88%) of insect viruses [18]. In line with the reckonings, the result displayed a practically similar constitution, as much as 84%, 82%, and 100% of viruses were insect viruses, or had a high correlation with the mosquito virome previously identified, in C. tritaeniorhynchus, C. pseudovishnui, and C. inatomii, respectively (Supplementary Figure S4), implying a consistent virome composition in Culex mosquitoes, with slight variations possibly associated with the number of samples used.…”
Section: Discussionmentioning
confidence: 99%
“…First strand cDNA synthesis, followed by labeling of cDNA and random amplification, was performed with 10 µl of RNA, as described by Cholleti et al 2016 [17]. The final amplified product were submitted to the National Genomics Centre (SciLife Lab, Uppsala, Sweden) for library preparation and sequencing.…”
Section: Cdna Labeling Amplification and Sequencingmentioning
confidence: 99%
“…During the past decade, advances in DNA sequencing technology have allowed the identification of a wide range of novel viruses associated with mosquitoes (Aguiar et al, 2015; Auguste et al, 2014; Bolling et al, 2015; Carissimo et al, 2016; Chandler et al, 2015; Charles et al, 2016; Cholleti et al, 2016; Coffey et al, 2014; Contreras-Gutierrez et al, 2017; Fauver et al, 2016; Frey et al, 2016; Li et al, 2015a; Li et al, 2015b; Nasar et al, 2012; Ng et al, 2011; Palacios et al, 2015; Pauvolid-Correa et al, 2016; Shi et al, 2015; Simmonds et al, 2017; Vasilakis et al, 2014a; Wang et al, 2015). We examine here, by electron microscopy and metagenomics analysis, 11 mosquito derived viral isolates from the extensive collection of the World Reference Center for Emerging Viruses and Arboviruses (WRCEVA) (https://www.niaid.nih.gov/research/wreceva), whose morphology indicated the likely presence of multi-segmented reoviruses.…”
Section: Introductionmentioning
confidence: 99%